Evaluation of the cultural ecosystem services of wetland park. (July 2020) - Zhou, Lilei; Guan, Dongjie; Huang, Xiaoyong; Yuan, Xingzhong; Zhang, Mengjie
Graphical abstract: Highlights: The 9 CES types of the wetland park were quantitatively evaluated by SolVES model. The gender of the respondents impacted the assessment of wetland CES. The background environmental variable was indirect driving factor of the CES value. Wetland was the most important environmental data for the CES of the wetland park. CES transfer from XNWP to GNUWP provided valid results. Abstract: One of effective ways to maintain and expand the protected area of wetlands is the development and construction of wetland parks. As urbanization increases, deep insight on the relationships between wetland cultural ecosystem services and natural environment has become critical. In this paper, we identified and mapped the cultural ecosystem services of two wetland parks (the Xiuhu National Wetland Park and the Guanyintang National Urban Wetland Park) by using the Social Values for Ecosystem Services model and the preference survey data. The results show that 1) the highest score of the cultural ecosystem services of Xiuhu National Wetland Park is the biodiversity perception value with a max value index of 10, and then future value and history value with a max value index of 9, aesthetic value and recreation value with a max value index of 8, and culture value, learning value, spiritual value and therapeutic value with a max value index of 7; 2) subjectively, the gender of the respondents affected the evaluation of cultural ecosystem services. The male prefers the aesthetic value, culture value, recreation value, spiritual value and therapeutic value, while female prefers the history value; 3) objectively, the cultural ecosystem services of wetland is affected by various environmental data layers; 4) the cultural ecosystem services values are transferred from Xiuhu National Wetland Park to Guanyintang National Urban Wetland Park, and the transferred value of Guanyintang National Urban Wetland Park has performed well. Our findings suggest that the Social Values for Ecosystem Services model is appropriate to serve such small-scale wetland park and our results can provide a scientific basis for wetland park managers and planners to optimize the cultural ecosystem services and protect wetland resources.